Endoscopic sleeve gastroplasty for obesity: A multicenter study of 248 patients with 24 months follow-up - Ahıshalı, Emel (Turkish Journal of Gastroenterology, 2018)
Abstract Cite this article as: Ahıshalı E. Endoscopic sleeve gastroplasty for obesity: A multicenter study of 248 patients with 24 months follow-up. Turk J Gastroenterol 2018; 29: 373-4.